Stability and change of attachment representations: the impact on the quality of mother-child attachment of pediatric epilepsy the first year after the diagnosis - Dimatis, Konstantinos; Vorria, Panagiota (Psychology: the Journal of the Hellenic Psychological Society, 2021)
A secure mother-child attachment early in life promotes healthy socio-emotional development. Security of attachment can be maintained through positive parental care over time. Life stresses can impact on maternal availability and sensitivity and lead to changes in attachment quality towards insecure patterns of attachment. The present study, which is part of a larger research project, aims to explore for the first time in a Greek population of preschool- and school-aged children and their mothers the impact of pediatric illness on stability and change of mother-child attachment representations. Twenty-five children, 9 boys and 16 girls, 4-9 years old with a recent diagnosis of epilepsy, were assessed using the Manchester Child Attachment Story Task (MCAST) at two time points, T1 and T2. Participants’ mothers completed the Social Support Questionnaire (SSQ) at both times (Τ1, Τ2). The results seem to confirm the stability and change of attachment representations during the first year after the diagnosis of epilepsy. The importance of perceived social support by mothers for positive change of mother-child attachment representations is also stressed by the authors.